Media Digital Monopoli untuk Meningkatkan Pembelajaran Sejarah Kelas X di SMA Negeri 19 Bekasi - Lelly Qodariah; Aditya Aditya (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Creative and innovative digital-based learning media can encourage students to improve their history learning process. This study aims to: (1) produce a monopoly learning media product on the theme of Introduction to History for class X students; (2) determine the feasibility of the developed monopoly history learning media based on expert validation; and (3) analyze the effectiveness of monopoly history learning media in improving the learning achievement of class X students at SMAN 19 Bekasi. The research method used is Research and Development (R&D) with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The subjects of the study were 20 students of class X.5 SMAN 19 Bekasi. Data collection techniques included validation sheets for media experts and material experts, as well as learning achievement tests (pre-test and post-test). Feasibility data analysis used descriptive percentage, while effectiveness data analysis used the Wilcoxon Signed Ranks Test. The results showed that: (1) an interactive PowerPoint-based monopoly history learning media product has been successfully developed; (2) The monopoly history learning media was declared highly feasible with a feasibility percentage from media experts of 96% and from material experts of 97.5%; (3) There was a statistically significant increase in students' history learning achievement after using the monopoly learning media (Z = -3.830; p < 0.001), where the average post-test score (17.35) was higher than the average pre-test score (11.70). It was concluded that the developed monopoly history learning media is feasible and effective as an alternative media to improve student learning achievement.